The Impact of Ownership Structure and Dividends on Firm’s Performance: Evidence from Manufacturing Companies Listed on the Amman Stock Exchange - Mo'taz Amin Abdulhameed Al-Sa'eed (Australasian Accounting, Business and Finance Journal, 2018)
This study aims to present empirical analysis from Amman Stock Exchange (ASE) to address the impact of ownership structure and dividends on the performance of Jordanian Manufacturing Companies. To test the study hypotheses and to achieve its objectives, the annual financial reports of all manufacturing companies and other related data during the period 2011 to 2015 were analyzed. Thus, Ownership structure and dividends are presented as independent variables, while the firm's performance is articulated as the dependent variable. It applies four diverse acceptable measurement tools as a proxy for the firm's performance (dependent variable); (Tobin's Q), (ROA), (ROE), and (NPM). The study found that the main variables (MO, CO, and DYLD) and the control variables (EPS and Total Assets) are good predictors of firm's performance. Also; the study found that (ROA) and (Tobin's Q) are the most representative indicators as proxies of the firm's performance. The study recommends considering another control variable to enhance predicting the firm's performance such as governance mechanisms, board structure, management competence, motivation-based payment structure, capital structure and external and internal auditing.
Keywords: Concentrated and management ownership; dividends; firm’s performance; Tobin’s Q; ROA; ROE; NPM.